2022
DOI: 10.3390/horticulturae8100890
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization of Pot-Grown Cichorium spinosum L.: How It Can Affect Plant Growth, Chemical Profile, and Bioactivities of Edible Parts?

Abstract: Cichorium spinosum L. is a perennial wild edible plant that is usually found near the coasts of the Mediterranean basin. In the present study, we evaluated the effect of the fertilization regime on the growth and chemical profile of pot-grown C. spinosum plants, as well as the effect of extraction protocol (aqueous and hydroethanolic extracts on bioactive properties). For this purpose, plants were fertilized via a nutrient solution that differed in the amounts (mg/L) of N:P:K, e.g., 100:100:100 (C111), 200:100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 66 publications
(104 reference statements)
5
9
1
Order By: Relevance
“…Our results indicate that apart from the increased amounts of nitrogen, the application of nutrient solution with balanced composition in P and K had a beneficial effect on fresh biomass yield, whereas excessive amount of macronutrients resulted in fresh yields similar to the untreated plants due to reduction in leaves number. These findings corroborate the aspect of minimum nutrients requirements for wild edible species, especially for the case of P and K, which were also confirmed by Polyzos et al [39] in Cichorium spinosum cultivation. Moreover, Papadimitriou et al [60] suggested that a high ratio of N:K (e.g., 2.38 mol/mol) in nutrient solution resulted in increased yields of leaves and roots in hydroponically grown Scolymus hispanicus compared to lower ratios (e.g., 1.59 mol/mol).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Our results indicate that apart from the increased amounts of nitrogen, the application of nutrient solution with balanced composition in P and K had a beneficial effect on fresh biomass yield, whereas excessive amount of macronutrients resulted in fresh yields similar to the untreated plants due to reduction in leaves number. These findings corroborate the aspect of minimum nutrients requirements for wild edible species, especially for the case of P and K, which were also confirmed by Polyzos et al [39] in Cichorium spinosum cultivation. Moreover, Papadimitriou et al [60] suggested that a high ratio of N:K (e.g., 2.38 mol/mol) in nutrient solution resulted in increased yields of leaves and roots in hydroponically grown Scolymus hispanicus compared to lower ratios (e.g., 1.59 mol/mol).…”
Section: Resultssupporting
confidence: 90%
“…Mean air temperature throughout the experimental period was as follows: October, 16.4 [61]. The tested fertigation treatments have already been described in detail in a similar study by our team regarding the commercial cultivation of Cichorium spinosum [39,52]. In brief, the applied treatments differed in the amounts of N:P:K, e.g., 100:100:100 (SH1), 200:100:100 (SH2), 200:200:200 (SH3), 300:100:100 (SH4), 300:200:200 (SH5) and 300:300:300 ppm (SH6) of N:P:K, as well as the control treatment without the addition of fertilizers (SHC).…”
Section: Plant Materials and Growing Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…One week prior to the harvest date, we measured plant height (cm), and photosynthetic rate (µmol CO 2 m −2 s −1 ) at a constant light intensity of 250 µmol cm −2 s −1 using the LI-Cor LI-6400XT Portable Photosynthesis System (LI-Cor, Lincoln, NE, USA)), whereas chlorophyll content (SPAD index) was measured using the OPTI-SCIENCES CCM-200 plus chlorophyll content meter (Opti-sciences, Hudson, NH, USA). Moreover, we measured the leaf area with the use of LI-3100C Area Meter (LI-COR Biosciences; Hellamco S.A., Athens, Greece) (all plant measurements are described in detail by [ 13 , 22 ]. At the end of the experiment, the aerial plant biomass was cut 2 cm above the soil surface and separated into leaves and stems.…”
Section: Methodsmentioning
confidence: 99%